Long non‐coding RNA TGLC15 advances hepatocellular carcinoma by stabilizing Sox4. Issue 1 (8th September 2019) - Chen, Yang; Huang, Fei; Deng, Liang; Tang, Yajun; Li, Dong; Wang, Tielong; Fan, Youwen; Tao, Qiang; Tang, Di
Abstract: Background: The hepatocellular carcinoma (HCC) belongs to a common malignancy especially in China. Recent data have clarified important roles of long non‐coding RNAs (lncRNAs) in HCC. However, the role of a novel intergenic lncRNA termed TGLC15 is still elusive. Methods: We screened for novel lncRNAs using lncRNA profiling. TGLC15 expression was quantified by qRT‐PCR. In vitro experiments such as migration and viability assays were performed. In vivo implantation experiments were conducted to investigate tumorigenic functions of TGLC15. Combined RNA immunoprecipitation (RIP) and mass spectrometry (MS) were utilized to uncover Sox4 as TGLC15 binding protein. Results: TGLC15 is significantly overexpressed in tumor tissues and HCC cell lines. Higher TGLC15 levels correlated with advanced malignant characteristics such as TNM stages, tumor size, and metastasis. TGLC15 advanced HCC migration and viability. The in vivo experiments supported that xenograft tumor growth and proliferation were facilitated by TGLC15 overexpression. Mechanistic studies showed that TGLC15 interacted with Sox4 and interaction between TGLC15 and Sox4 could stabilize Sox4 via reduction in proteasome‐mediated degradation. Conclusions: Collectively, our data have identified a novel lncRNA TGLC15 during HCC development. The TGLC15‐Sox4 signaling might be a potential target for pharmaceutical intervention.